In vivo phagocytosis and hematology in astyanax altiparanae, a potential model for surrogate technology - Levy-Pereira, N. [UNESP]; Yasui, G. S. [UNESP]; Evangelista, M. M. [UNESP]; Nascimento, N. F. [UNESP]; Santos, M. P. [UNESP]; Siqueira-Silva, D. H.; Monzani, P. S.; Senhorini, J. A. [UNESP]; Pilarski, F. [UNESP] (FapUNIFESP (SciELO), 2020)
Although the potential of surrogate propagation technology for aquaculture and conservation of Neotropical fish, the poor understanding of the host immune system may results in rejection and destruction of the donor material. Thus, it is necessary to study and to develop methods to evaluate the effects of immunosuppressive drugs employment and to evaluate the immunocompatibility between donor and receptor. Thus, the present study aimed to optimize a methodology to assess in vivo phagocytosis in Astyanax altiparanae using Saccharomyces cerevisiae and to evaluate their hematological response resultant from the inflammatory induction. To this, S. cerevisiae were labeled with Congo red and injected in the coelomic cavity of A. altiparanae at the concentration of 2.5 x 106 cells mL-1. A PBS solution and a non-injected group were kept as control. Fish blood was sampled and the phagocytic capacity and index were determined at 1, 2, 3 and 6 h post-injection (hpi). The yeast injection successfully stimulated phagocytosis, with the best result for phagocytosis assessment after 2 hpi. Moreover, it was achieved a high traceability of phagocytized and non-phagocytized yeast under optic microscopy analysis due to the Congo red labeling. The hematological profile was similar to usually observed in early infections, indicating lymphocyte migration to inflammatory site and increase in number of circulating phagocytes due to natural response to inflammatory stimulus. In conclusion, our method was efficient to assess in vivo phagocytosis in A. altiparanae and will be an important tool to evaluate the efficacy of immunosuppressive drugs in this species. Additionally, these results may serve as support for further studies in fish immunocompetence, both in laboratory and in field conditions.
Fagocitose in vivo e hematologia em astyanax altiparanae, um potencial modelo para tecnologia de propagação mediada
Keywords: Hematology; Innate immune response; Neotropical fish; Surrogate technology host